2018
DOI: 10.1002/ird.2234
|View full text |Cite
|
Sign up to set email alerts
|

Water Management to Enhance Ecosystem Services in a Coastal Wetland in Taiwan

Abstract: Wetlands provide multiple ecosystem services, and wetland hydrology is one of the key determinants of wetland function. Budai Salt Pan Wetland provides at least 11 ecosystem services, i.e. food provision, genetic materials, climate regulation, water purification and treatment, natural hazard regulation, pollination, spiritual and inspirational, recreational, aesthetic, educational and nutrient cycling. As the wetland is completely encompassed by dikes, there is no natural hydrological connectivity, and the wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Due to excessive groundwater extraction, land subsidence occurs in wetland region. And its altitude is -1.8~-0.5m currently [26] . Moreover, Rice, sugar, and tea are three famous traditional products in Taiwan, each of them known as the "Three Treasures of Taiwan".…”
Section: Study Areamentioning
confidence: 99%
“…Due to excessive groundwater extraction, land subsidence occurs in wetland region. And its altitude is -1.8~-0.5m currently [26] . Moreover, Rice, sugar, and tea are three famous traditional products in Taiwan, each of them known as the "Three Treasures of Taiwan".…”
Section: Study Areamentioning
confidence: 99%
“…In this area, several unique coastal ecosystems exist, such as lagoons, sandbars, large-scale intertidal wetlands, and estuary wetlands. Coastal ecosystems can provide diverse ESs in these areas of Taiwan (Lew & Wu 2017, Kuo & Wang 2018, Hsu 2019. Additionally, these regions represent good habitats for rare migratory birds (e.g.…”
Section: Research Areamentioning
confidence: 99%
“…Other techniques to control the water levels in coastal wetlands are the use of dikes and water gates. Recently, tidal gate management approaches, together with tidal surge fluctuations, are being used to accomplish water management objectives (Kuo and Wang 2018, Vinten et al 2019, Khalil et al 2020, Wang et al 2020, Gaydon et al 2021, Guiot et al 2023. Vinten et al (2019) assessed the potential for hydraulic structure and dredging to manage water inflow and nutrient input into shallow wetlands in Scotland and to promote an adaptive water management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the influence of ecology, water level, and salt-water intrusion controls all needed to be considered in the water management plan to obtain a water flow regime appropriate for fish passage (Guiot et al 2023). In Taiwan, the short-term use of water gates was synchronized with tidal cycles to enhance bird habitat, water flow, flood mitigation, and other ecosystem services in the Budai Saltpan Wetlands (Kuo andWang 2018, Wang et al 2020), allowing increasing use by water birds by manipulating water depths while maintaining public safety in the surrounding village communities. Stakeholder experiences also demonstrated https://www.ecologyandsociety.org/vol28/iss3/art4/ the importance of considering communities' local needs in water management.…”
Section: Introductionmentioning
confidence: 99%